Effects of Zinc Source on Growth Performance and Carcass Characteristics of Finishing Pigs - Maxwell L. Corso; Jason C. Woodworth; Mike D. Tokach; Jordan T. Gebhardt; Robert D. Goodband; Joel M. DeRouchey; Chris van de Ligt (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 3,159 pigs (PIC 337 × 1050; initially 48.2 ± 1.70 lb) were used to determine the effect of Zn source on growth performance, carcass characteristics, and within-pen BW and HCW variation. Pigs were housed in mixed-gender pens with 27 pigs per pen and 39 pens per treatment across three barns. Individual pig weights were taken at allotment, first marketing, and final marketing to calculate within-pen body weight variation. Experimental treatments consisted of diets containing 100 ppm of Zn from: 1) Zn hydroxychloride; 2) ZnSO4, or 3) ZnO. Data were divided into three phases, encompassing three time periods, phase 1 from approximately 50 to 120 lb, phase 2 from 120 to 200 lb, and phase 3 from 200 to 300 lb. During period 1, pigs fed diets with ZnO had improved (P < 0.05) ADG and F/G compared to those fed the diet containing Zn hydroxychloride. In period 2, Zn source had no effect on ADG, ADFI, or F/G (P > 0.10). During period 3, pigs fed diets containing Zn hydroxychloride had improved (P < 0.05) ADG and F/G compared to those fed the diet containing ZnO. Overall, there were no differences (P > 0.10) observed for growth performance or carcass characteristics. Furthermore, Zn source did not affect BW or HCW variation. In conclusion, pigs fed the three Zn sources had similar overall growth performance, carcass characteristics, and weight variation.
Keywords: grow-finish pig; weight variation; zinc source